Environmental performance of budget hotels in Pakistan: Nexus of environmental orientation, eco-innovation and competitive intensity - Muhammad Tariq; Muhammad Yasir; Abdul Majid (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2021)
The current study aims to investigate the influence of budget-hotels' environmental orientation (EO) on their eco-innovation (EI) and environmental performance (EP). Besides empirically testing the said direct relationship, mediating role of EI in the relationship between EO and EP has also been investigated. Moderating effect of competitive intensity (CI) of the firm has also been examined on the link between EI and EP. The requisite data for this study was collected from 422 individuals, working on various managerial positions in the budget-hotels in Pakistan. Correlation, path analysis, structural equation modelling and hierarchical regression were used for the purpose of data analysis. Data analysis using SPSS and AMOS reveals a direct effect of EO on EI and EP. Moreover, the results substantiated that EI mediates between EO and EP. Moderating effect of CI on the link between EI and EP has also been confirmed. The study advocates new mechanisms which would be helpful in protecting natural environment. In the context of budget hotel segment of hospitality industry of Pakistan, the present study makes significant contribution to the literature through knowledge addition regarding the positive association of EO and EI.
Keywords: 330; environmental orientation; eco-innovation; environmental performance; competitive intensity; budget-hotel; covid-19; Pakistan